Long-term impact of olfactory dysfunction on daily life - Auinger, Alice B.; Besser, Gerold; Liu, David T.; Renner, Bertold; Mueller, Christian A. (Wiener Klinische Wochenschrift, 2020)
Background: Olfactory dysfunction (OD) is common in the general population, affects the quality of life (QoL), and is suspected to cause depression. Long-term outcome data are lacking and there is a need to improve patient counselling regarding prognosis. We aimed to assess subjective long-term recovery rates, the QoL, and mood disturbance in a group of 65 patients, who were affected with OD. Methods: Out of 325 patients treated for OD between 2003 and 2009 at a smell and taste clinic, 65 patients were included for a follow-up after an average of 8.6 years. A total of 28 patients answered questionnaires only and 37 patients were provided with an additional smell identification test. Among others, questionnaires included a short form of the World Health Organization quality of life questionnaire (WHOQOL-BREF) and the Beck’s depression inventory. Results: In the long run, subjective improvement was stated in 33.8% of all patients, with the highest rate of 42.3% in patients with postinfectious OD. The subjective rating of olfactory function on a visual analogue scale was significantly higher at study follow-up compared to first clinical contact (median 1.25 vs. 4.5; U = 469.5, p = 0.001), as were mean identification scores (6.0 ± 3.0 vs. 8.0 ± 4.0, t(18) = 2.51, p = 0.021). The QoL in general was considered reduced in 40% of all patients at follow-up. Furthermore, participants exhibited only minor, if any, depressive symptoms. Conclusion: Despite negative effects of OD on certain activities in daily life, such as cooking, detecting spoiled food, or personal hygiene, it seems that the patients included in this study adapted to the OD in the long-term. The current findings should aid clinicians in patient counselling.
CRIS-Team Scopus Importer:2020-10-30
Keywords: Anosmia; Hyposmia; Prognosis; Quality of life; Smell